A study on the knowledge, attitude and practice on adverse drug reactions and pharmacovigilance among post graduate residents in Gandhi Medical College, Bhopal - Hindoliya, Mukesh; Chitapure, Faizan (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Resident doctors should consider adverse drug reaction (ADR) reporting as their professional obligation and should be aware of the existing pharmacovigilance mechanisms in their countries. In India, pharmacovigilance implementation is essential due to the absence of a vibrant ADR monitoring system. The present study primary objective was to evaluate the knowledge, attitude and practices (KAP) of the postgraduate students towards pharmacovigilance and ADR reporting in GMC, Bhopal as they observe and attend to the patients round the clock while the patient is admitted in the hospital. Methods: A cross-sectional-observational study was carried out using a pretested questionnaire having 17 questions in all. Data was compiled, entered in Microsoft Excel sheet and analysed by descriptive statistics. Results: A total of 127 duly filled responses were analysed. Study shows ADR is necessary and Pharmacovigilance should be taught in detail to postgraduate students is an important finding from our study. In this study there was also a wide gap between the ADR experienced in professional practice (71%) and ADR reported (23%). Conclusions: In our present study, the average knowledge score was 64% in contrast to 32% residents who didn’t answered correctly. Though majority (87%) of the residents had a positive attitude towards awareness about Pharmacovigilance and ADR reporting, however in clinical scenario even as ADR reporting was considered to be important by a large majority of the participants, the actual practices of ADR reporting was very low.